Yahoo Web Search

  1. Ad
    related to K.C
  1. Sort by

  1. ...two vectors. Does it make sense? Yes, it's another vector. k(a-b) x (a x c) is the cross product of two vectors. Does it make sense? ...

    1 Answers · Science & Mathematics · 15/07/2016

  2. Using the binomial theorem (sqrt(2)-1)^k = C sqrt(2) - D where C and D ...1) = Csqrt(2) - D then (sqrt(2)-1)^k = -(C+D)sqrt(2) + (2C+D) If...

    2 Answers · Science & Mathematics · 30/10/2008

  3. They lie on a straight line if the gradient of AB equals the gradient of BC So (4-k)/4 = (1-3k-4)/2 Maybe you can take it from there !

    2 Answers · Science & Mathematics · 01/04/2010

  4. You didn't kill the f off when you put the squared sign in and also there's no reason for the minus sign of x-1 to randomly become a plus... Thus y=7(-1/6(x-1))^2+1 is what you're after. So y=7(1/36(x-1)(x-1)) and tbh I wouldn't much bother with multiplying that out '...

    1 Answers · Science & Mathematics · 06/03/2012

  5. QE : 1x² + (-k)x + (2k-10) = 0 ∴ a = 1, b = -k, c = 2k - 10 .......... (1) For equal roots, discriminant Δ = b²...

    1 Answers · Science & Mathematics · 09/04/2011

  6. Yes it is the same . Just like y = mx+b is the same as y = b+mx We just usually write the vertical shift last, since it's the last computation. Hoping this helps!

    4 Answers · Science & Mathematics · 01/09/2011

  7. Those two interpretations are equivalent, and they are both correct. Let me explain something with a simpler example. Begin with the graph of this equation: y = f(x) Transform it to this: y = -2f(x) This typically is...

    2 Answers · Science & Mathematics · 23/10/2016

  8. ... the binomial probability formula: P(X = k) = C(n,k) * p^k * q^(n-k) n : number of ...5,3) * 0.08^3 * 0.92^2 = ... P(X=4) = C(5,4) * 0.08^4 * 0.92^1 = ... P(X=5...

    2 Answers · Science & Mathematics · 12/01/2017

  9. There are 100000 cm in a km

    20 Answers · Science & Mathematics · 21/07/2006

  10. In the first one you need to evaluate the equation for x = 0 to find the y-intercept. y = a(0-p)^2 + q y = ap^2 + q this will be the y -intercept You can do the same in the second, but it will be "c", yes.

    1 Answers · Science & Mathematics · 11/02/2008

  1. Ad
    related to K.C
  1. Try asking your question on Yahoo Answers